Geostatistical Assessments for Characteristics of Soils Around Naip Dam (International Journal of Scientific Research and Management (IJSRM), 2019)
Investigation and mapping spatial variations (distance-dependent variations) in soil characteristics with the aid of geostatistical methods will bring about significant savings for labor, time and cost in agricultural practices. From this point forth, this study was conducted around Naipköy dam to determine spatial distribution of physical and chemical soil characteristics. Soil samples were taken from both sides of Tekirdağ Ganos Mountain (the side towards Naip plain and the side towards Marmora Sea). The research site was divided into 1000 x 2000 m grids and disturbed samples were taken from 0-30 cm soil profile of 24 points. Soil samples were subjected to texture, organic matter, pH, EC, calcium, magnesium, potassium and phosphorus analyses. Analyses revealed that the sections towards Naip plain had quite high clay and silt contents because of clayey deposition over these sections. These samples also had high calcium and thusly pH values because of lime layers of these sections. Soil properties were mapped in ArcGIS/ArcMAP 10.6 software with the aid of Inverse Distance Weighting (IDW) method. The maps generated facilitated assessments made for the relationships between land use and physico-chemical soil characteristics. Statistical analyses revealed the least coefficient of variation (8.44%) for pH and the greatest coefficient of variation (73.51%) for phosphorus.